Performance comparison of different electron transport layer for perovskite solar cell with NiO as hole transport layer using SCAPS 1D - Norddin, Nurbahirah; Shafie, Suhaidi; Idris, Muhammad Idzdihar; Liu, Xinzhi; Lawal, Ismail; Rummaja, Mohd Iskandar Dzulkarnain M.; Abdul Aziz, Ahmad Muhajer; Nor, Rozilawati Mohd (2023)
Perovskite solar cells have garnered significant attention from solar cell researchers due to their potential for achieving high efficiency. There is promising avenue for enhancing stability and reducing fabrication costs by substituting the transport layer. Comparative analysis was conducted between two devices featuring distinct structures: TiO2/CH3NH3PbI3/NiO and ZnO/CH3NH3PbI3/NiO. To evaluate the performance of each electron transport layer (ETL), the SCAPS 1D tool was employed. The investigation involved varying the thickness of the absorber, electron transport layer, and hole transport layer, allowing for a comprehensive assessment of key parameters such as voltage at open circuit (Voc), short circuit current density (Jsc), fill factor (FF), and overall efficiency (PCE%). When employing TiO2 as the ETL, the achieved efficiency stands at 24.08%. In contrast, utilizing Zinc Oxide (ZnO) as the ETL yields a slightly higher efficiency of 24.29%. These findings show influence of transport layer materials to overall performance of perovskite solar cells.